Customer intention towards self-service checkout at Watson - Mohd Arzaman, Ameer Farhan; Abdul Rashid, Nurulizwa; Razali, Muhamad Amirul; Jospat, Anisah; Abdul Aziz, Noor Aisyah; Damaianti, Indriana (Malque Publishing, 2024)
This research focuses on customers intentions to use the self-checkout technology at Watson during the Covid19 endemic using UTAUT2 model. The main objective is to identify the factors that affect the behavioral intention to use the self-checkout technology from a consumer perspective. This study investigated the influencing factors of performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, and habit towards customers' intention to use the self-checkout systems. The data for this study were collected using a questionnaire shared among 200 respondents who are Watson customers were selected by stratified random sampling technique through online. The data were analyzed using IBM- SPSS version 26 to test the hypotheses. The findings indicate that customers intention is significantly and positively influenced by performance expectancy, effort expectancy, facilitating condition, hedonic motivation and habit behaviour. A number of implications for theory and practice are derived based on the findings.